Smoking and epilepsy in national health interview survey: a cross-sectional study - Huang, Xiaoping; Liu, Qi; Zhao, Qingya; Ji, Qianqian; Zhan, Yiqiang (Frontiers in Human Neuroscience, 2025)
ObjectiveThis study aimed to examine the association between smoking and epilepsy in a nationwide cross-sectional analysis of US adults.MethodsData from the National Health Interview Survey (NHIS) conducted between 2021 and 2022 were utilized, encompassing 57,088 participants aged 18–85 years with documented tobacco usage and self-reported epilepsy. Logistic regression models were employed to evaluate the relationship between smoking and epilepsy. The assessment of tobacco usage encompassed smoking status, cigarette smoking, pipe-filled tobacco smoking, and smokeless tobacco usage.ResultsThe overall prevalence of self-reported epilepsy in the sample was 1.76%, with smokers constituting 46.03% of cases. Individuals with epilepsy exhibited higher smoking rates compared to those without epilepsy. In the multivariate logistic regression model, smoking demonstrated a significant association with self-reported epilepsy (OR = 1.26, 95% CI: 1.07–1.47, P = 0.005). Subsequent stratified analyses showed consistent associations between smoking and self-reported epilepsy in all sex and ethnic subgroups.ConclusionsOur findings suggest that smoking is independently associated with self-reported epilepsy among US adults. Further investigation into the biological mechanisms underlying this association is warranted, contingent upon the validation of these results in an external population.